Documented information and knowledge management in ISO 9001: 2015: Contribution of the information professional - García-Morales, Elisa (Anuario ThinkEPI, 2017)
2016 has been a year in which many companies have undertaken the adaptation of the new ISO 9001:2015 "Quality management systems". Based on the practical experience of the accreditation process by a large multinational engineering company, the author reflects on the role of information professionals in the implementation of the Knowledge Management and Documented Information sections of the standard.
Keywords: Documented information; Knowledge management; ISO 9001; 2015; Records management.